Stem cell derived phenotypic human neuromuscular junction model for dose response evaluation of therapeutics. (June 2018) - Santhanam, Navaneetha; Kumanchik, Lee; Guo, Xiufang; Sommerhage, Frank; Cai, Yunqing; Jackson, Max; Martin, Candace; Saad, George; McAleer, Christopher W.; Wang, Ying; Lavado, Andrea; Long, Christopher J.; et al.
Abstract: There are currently no functional neuromuscular junction (hNMJ) systems composed of human cells that could be used for drug evaluations or toxicity testing in vitro . These systems are needed to evaluate NMJs for diseases such as amyotrophic lateral sclerosis, spinal muscular atrophy or other neurodegenerative diseases or injury states. There are certainly no model systems, animal or human, that allows for isolated treatment of motoneurons or muscle capable of generating dose response curves to evaluate pharmacological activity of these highly specialized functional units. A system was developed in which human myotubes and motoneurons derived from stem cells were cultured in a serum-free medium in a BioMEMS construct. The system is composed of two chambers linked by microtunnels to enable axonal outgrowth to the muscle chamber that allows separate stimulation of each component and physiological NMJ function and MN stimulated tetanus. The muscle's contractions, induced by motoneuron activation or direct electrical stimulation, were monitored by image subtraction video recording for both frequency and amplitude. Bungarotoxin, BOTOX ® and curare dose response curves were generated to demonstrate pharmacological relevance of the phenotypic screening device. This quantifiable functional hNMJ system establishes a platform for generating patient-specific NMJ models by including patient-derived iPSCs. Highlights: A system in which stem cell derived human myotubes and MNs were cultured in a serum-free medium in a BioMEMS construct. Directed axonal outgrowth links muscle and MN chambers to allow for physiological NMJ function and MN stimulated tetanus. The muscle's contractions were monitored by image subtraction video recording for both frequency and amplitude. Bungarotoxin, BOTOX ® and curare dose response curves were generated for pharmacological relevance of the phenotypic screen. This hNMJ system establishes a platform for generating patient-specific models using iPSCs for personalized medicine.